How might acupuncture work? A systematic review of physiologic rationales from clinical trials - Moffet Howard H (BMC, 2006)
Abstract Background Scientific interest in acupuncture has led numerous investigators to conduct clinical trials to test the efficacy of acupuncture for various conditions, but the mechanisms underlying acupuncture are poorly understood. Methods The author conducted a PubMed search to obtain a fair sample of acupuncture clinical trials published in English in 2005. Each article was reviewed for a physiologic rationale, as well as study objectives and outcomes, experimental and control interventions, country of origin, funding sources and journal type. Results Seventy-nine acupuncture clinical trials were identified. Twenty-six studies (33%) offered no physiologic rationale. Fifty-three studies (67%) posited a physiologic basis for acupuncture: 33 (62% of 53) proposed neurochemical mechanisms, 2 (4%) segmental nervous system effects, 6 (11%) autonomic nervous system regulation, 3 (6%) local effects, 5 (9%) effects on brain function and 5 (9%) other effects. No rationale was proposed for stroke; otherwise having a rationale was not associated with objective, positive or negative findings, means of intervention, country of origin, funding source or journal type. The dominant explanation for how acupuncture might work involves neurochemical responses and is not reported to be dependent on treatment objective, specific points, means or method of stimulation. Conclusion Many acupuncture trials fail to offer a meaningful rationale, but proposing a rationale can help investigators to develop and test a causal hypothesis, choose an appropriate control and rule out placebo effects. Acupuncture may stimulate self-regulatory processes independent of the treatment objective, points, means or methods used; this would account for acupuncture's reported benefits in so many disparate pathologic conditions.